Structural and Raman spectroscopic studies of the two M0.50SbFe(PO4)3 (M = Mg, Ni) NASICON phases. (2nd May 2017) - Aatiq, Abderrahim; Marchoud, Asmaa; Bellefqih, Hajar; Tigha, My Rachid
Abstract : Structures of the two M 0.50 SbFe(PO4 )3 ( M = Mg, Ni) phases, abbreviated as [Mg0.50 ] and [Ni0.50 ], were determined at room temperature from X-ray diffraction (XRD) powder data using the Rietveld analysis. Both compounds belong to the NASICON structural family. XRD patterns of [Mg0.50 ] and [Ni0.50 ] phases were easily indexed with a primitive hexagonal unit cell [ P $\overline 3 $ space group, Z = 6] similar to that already obtained for La0.33 Zr2 (PO4 )3 . Obtained unit cells parameters are [ a = 8.3443(1) Å, c = 22.3629(1) Å], and [ a = 8.3384(1), c = 22.3456(1) Å], respectively, for [Mg0.50 ] and [Ni0.50 ] phosphates. In both samples, the [Sb(Fe)(PO4 )3 ] − NASICON framework is preserved and a partially-ordered distribution of Sb 5+ and Fe 3+ ions is observed. Raman spectroscopic study was used to obtain further structural information about the nature of bonding in [Mg0.50 ] and [Ni0.50 ] phases.